VEGF‐B signaling impairs endothelial glucose transcytosis by decreasing membrane cholesterol content. (24th May 2020) - Moessinger, Christine; Nilsson, Ingrid; Muhl, Lars; Zeitelhofer, Manuel; Heller Sahlgren, Benjamin; Skogsberg, Josefin; Eriksson, Ulf
Abstract: Regulation of endothelial nutrient transport is poorly understood. Vascular endothelial growth factor B (VEGF‐B) signaling in endothelial cells promotes uptake and transcytosis of fatty acids from the bloodstream to the underlying tissue, advancing pathological lipid accumulation and lipotoxicity in diabetic complications. Here, we demonstrate that VEGF‐B limits endothelial glucose transport independent of fatty acid uptake. Specifically, VEGF‐B signaling impairs recycling of low‐density lipoprotein receptor (LDLR) to the plasma membrane, leading to reduced cholesterol uptake and membrane cholesterol loading. Reduced cholesterol levels in the membrane leads to a decrease in glucose transporter 1 (GLUT1)‐dependent endothelial glucose uptake. Inhibiting VEGF‐B in vivo reconstitutes membrane cholesterol levels and restores glucose uptake, which is of particular relevance for conditions involving insulin resistance and diabetic complications. In summary, our study reveals a mechanism whereby VEGF‐B regulates endothelial nutrient uptake and highlights the impact of membrane cholesterol for regulation of endothelial glucose transport. Synopsis: This study identifies a relationship between plasma membrane cholesterol content and glucose transport capacity in endothelial cells, which is regulated by VEGF‐B signaling. VEGF‐B signaling in endothelial cells impairs recycling of LDLR to the plasma membrane, leading to reduced cholesterol uptake and membrane cholesterol loading. Reduced membrane cholesterol loading decreases the rate of endothelial glucose uptake via GLUT1, restricting tissue glucose availability. VEGF‐B inhibition in vivo reconstitutes membrane cholesterol content and restores endothelial glucose uptake and tissue glucose availability. Abstract : This study identifies a relationship between plasma membrane cholesterol content and glucose transport capacity in endothelial cells, which is regulated by VEGF‐B signaling.